1973
DOI: 10.1002/qj.49709942014
|View full text |Cite
|
Sign up to set email alerts
|

Momentum and mass transfers in the surface boundary layer

Abstract: SUMMARYResults are presented from six micrometeorological studies conducted over a grass turf at Davis, California, in 1066 and 1967. Highly reliable surface drag and evaporation data from very sensitive lysimeters of 6.1 m diameter afforded excellent opportunity to evaluate several parameters important to aerodynamicprediction equations.For the six studies the mean von Kirman constant, k, ranged from 0-40 to 0 4 4 , strongly supporting continued acceptance of k at around 0.42.The Monin-Obukhov (1954) universa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
1

Year Published

1974
1974
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(45 citation statements)
references
References 22 publications
1
43
0
1
Order By: Relevance
“…Other experiments on air temperature (C=T ) and water vapor (C=q) exchange from different geographic regions around the world are also presented for illustration (as symbols). These experiments include the influential Kansas data [4], the data collected in the towns of Kerang and Hay [5] on heat and water vapor exchange in Australia, the data on heat exchange over the Pampas in Brazil [6], the long-term (day-time only) heat exchange data from the Steppe region in Russia [7], the long-term data on heat exchange from the island of Gotland in the Baltic Sea [8], data for water vapor exchange using drag plate (to estimate u * ) and weighing lysimeter (to estimate water vapor fluxes) from University of California Davis, California, USA [9]. pressure, respectively, ρ is the mean air density, ν is the air kinematic viscosity, D m is the molecular diffusivity of scalar C in air, u ′ i = (u ′ , v ′ , w ′ ) are the componentwise turbulent velocity excursions in direction x i , c ′ is the turbulent scalar concentration fluctuation, and unless otherwise stated, primed quantities represent turbulent excursions from the Reynolds-averaged mean state represented by overbar or capital letter symbols.…”
Section: Theorymentioning
confidence: 99%
“…Other experiments on air temperature (C=T ) and water vapor (C=q) exchange from different geographic regions around the world are also presented for illustration (as symbols). These experiments include the influential Kansas data [4], the data collected in the towns of Kerang and Hay [5] on heat and water vapor exchange in Australia, the data on heat exchange over the Pampas in Brazil [6], the long-term (day-time only) heat exchange data from the Steppe region in Russia [7], the long-term data on heat exchange from the island of Gotland in the Baltic Sea [8], data for water vapor exchange using drag plate (to estimate u * ) and weighing lysimeter (to estimate water vapor fluxes) from University of California Davis, California, USA [9]. pressure, respectively, ρ is the mean air density, ν is the air kinematic viscosity, D m is the molecular diffusivity of scalar C in air, u ′ i = (u ′ , v ′ , w ′ ) are the componentwise turbulent velocity excursions in direction x i , c ′ is the turbulent scalar concentration fluctuation, and unless otherwise stated, primed quantities represent turbulent excursions from the Reynolds-averaged mean state represented by overbar or capital letter symbols.…”
Section: Theorymentioning
confidence: 99%
“…That research has generally shown that airflow is logarithmic and enhanced within the boundary layer above the canopy, and exponential and retarded within the canopy (Plate & Quraishi 1964, Cionco 1965, Businger et al 1971, Oliver 1971, Pruitt et al 1973, Businger 1975, Hartog & Shaw 1975, Legg & Monteith 1975, Seginer et al 1976, Raupach & Thom 1981. I adapted these profiles to my model and defined the appropriate parameters for eelgrass canopies.…”
Section: The Modelmentioning
confidence: 99%
“…The turbulent transfer coefficient for vapour, KE, could be greater than that for momentum, KM. Pruitt et al (1973) derived the relation of KE=1.13KM (with k= 0.42), and Yasuda and Toya (1988) obtained the result of KE=1.3KM (with k=0.4) based on the careful turbulent and vertical profile measurements conducted at the paddy field after harvest. In the work of Lettau and Davidson (1957), Lettau and Halstead referred to this question.…”
Section: Results Of Simulation and Discussionmentioning
confidence: 99%